Implications of The New Gwadar Smart Port City Master Plan: A plan for the Rights of Local People? - Jamali, Hafeez Ahmed (Journal of Pakistan Administration, 2020)
Gwadar City has been a lynchpin of the Government of Pakistan's plans for modernizing its economy and projecting its economic and military power into the Persian Gulf region since the start of work on Gwadar Deep Water Port Project in 2002. Gwadar caught the attention of Pakistani and Chinese policymakers due toupgra its pivotal location near the entrance to the Persian Gulf through which one third of the world's oil supplies pass and for its potential as a terminal for North‐South transportation of oil and gas from the landlocked Central Asian countries and western parts of China.2 Since the early 1990s, Pakistan has considered Gwadar a cornerstone of its strategy to increase its economic and military clout in the Middle East and Southwest Asia. US$ 248 Million were spent in building the ﬁrst phase of Gwadar Deep Water Port Project with technical and ﬁnancial assistance from China (Government of Pakistan 2005). The ﬁrst phase of Gwadar Port was completed in 2007 and its operation and maintenance were handed over to the Port Authority of Singapore (PSA) through an open international bidding process. Its operation was subsequently handed over to China Overseas Port Holding Corporation (COPHC) on Build Operate Transfer (BOT) basis in 2013 as a precursor to the signing of China Pakistan Economic Corridor.
Keywords: Smart Port City; Master Plan; Local People; Build Operate Transfer (BOT); China Overseas Port Holding Corporation (COPHC)